Harmonization of State Receivables Management Arrangements : Perspective of Authority Theory and Hierarchy Theory of Legislative Regulations - Aritonang, Syofina Dwi Putri (Reformasi Hukum, 2024)
PP No. 28 of 2022 in its implementation creates overlapping norms with the legal provisions above, namely, with several articles in the 1945 Constitution of the Republic of Indonesia, the Human Rights Law and the Civil Code which ultimately creates legal uncertainty. Based on the urgency of the problem, this research aims to find a solution to the conflict of norms that occurs through harmonization of statutory regulations. This research uses normative research methods with a statutory and conceptual approach. Meanwhile, the legal materials used are primary and secondary legal materials through literature study which will be analyzed using argumentative techniques. The results of this research indicate that there has been an overlap in norms from the implementation of PP No. 28 of 2022, therefore it is necessary to immediately carry out improvements to the PP by the competent authorities. However, in addition to amending the PP, the public can also play an active role by submitting a judicial review of PP No. 28 of 2022 to the Supreme Court.